Peningkatan literasi bahaya narkoba pada siswa SMP Negeri 5 Kandis dan SMA Negeri 2 Kandis - Razkia, Dwita; Juliharsyah, Arya Dwi; Wardani, Kurnia Vera; Pratiwi, Tri Rahayu; Yusnira, Dina; Rivaldo, Leoky; Cahyaningrum, Eunike Danis; Azani, M Teja; Dewi, Ratna Sari; Saragih, Rendra Deardo; Pratama, Arya Sapta; Rahmawati, Aci; Chantika, Bunga; Darini, Darini (Penamas: Journal of Community Service, 2025)
Drug abuse poses a serious threat to Indonesia's young generation, particularly among junior and senior high school students who are highly vulnerable to peer influence. As a form of community service, the Community Service Program (KKN) team conducted a drug abuse awareness campaign at SMPN 5 Kandis (400 students) and SMAN 2 Kandis (500 students) on September 3, 2025. The activity involved 13 students from the Belutu Village KKN group in collaboration with village officials, healthcare workers, and school representatives. The implementation methods included a pre-test, interactive lectures, group discussions, Q&A sessions, and a post-test to measure improvement in students' understanding. The results showed a significant increase in the "good" knowledge category, from 20% in the pre-test to 80% in the post-test, while the "poor" category dropped sharply from 40% to 5%. In addition, students demonstrated positive behavioral changes by committing to staying away from drugs and reminding their peers to do the same. These findings indicate that a multi-stakeholder synergy between university students, local communities, schools, village authorities, and healthcare workers is effective in improving drug abuse literacy among adolescents.